2009
DOI: 10.1111/j.1469-8137.2009.02978.x
|View full text |Cite
|
Sign up to set email alerts
|

GintPDX1 encodes a protein involved in vitamin B6 biosynthesis that is up‐regulated by oxidative stress in the arbuscular mycorrhizal fungus Glomus intraradices

Abstract: Summary• Vitamin B6 is an essential metabolite that has recently been implicated in defense against cellular oxidative stress. In fungi, the de novo biosynthetic pathway of vitamin B6 involves two genes, PDX1 and PDX2. Here, we report a component of the PDX1/ PDX2 vitamin B6 biosynthetic pathway in an arbuscular mycorrhizal (AM) fungus.• Using rapid amplification of cDNA ends, we isolated the full-length cDNA of a PDX-like gene, GintPDX1, from Glomus intraradices. GintPDX1 expression was analysed by real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 78 publications
2
32
0
Order By: Relevance
“…Additionally, it was shown that cercosporin-sensitive mutant strains can be rescued by complementation with the pdx1 gene of Phaseolus vulgaris [46]. Similar results were observed with a pdx1 (snz1)-deficient Saccharomyces cerevisiae strain which could be complemented with the pdx1 gene of the arbuscular mycorrhizal fungus Glomus intraradices (Gintpdx1) [47]. It has been shown that vitamin B 6 -deficient mutants of Arabidopsis thaliana are highly sensitive against high light and photo-oxidative stress due to the formation of 1 O 2 and the resulting severe lipid peroxidation [48].…”
Section: Discussionsupporting
confidence: 62%
“…Additionally, it was shown that cercosporin-sensitive mutant strains can be rescued by complementation with the pdx1 gene of Phaseolus vulgaris [46]. Similar results were observed with a pdx1 (snz1)-deficient Saccharomyces cerevisiae strain which could be complemented with the pdx1 gene of the arbuscular mycorrhizal fungus Glomus intraradices (Gintpdx1) [47]. It has been shown that vitamin B 6 -deficient mutants of Arabidopsis thaliana are highly sensitive against high light and photo-oxidative stress due to the formation of 1 O 2 and the resulting severe lipid peroxidation [48].…”
Section: Discussionsupporting
confidence: 62%
“…The efficiency of the primer sets was evaluated by performing Real-Time PCR on several dilutions of DNA. The results obtained for the different treatments were standardized to the elongation factor 1-alpha (GintEF1a) gene levels (Benabdellah et al, 2009). Real Time RT-PCR determinations were performed on at least two independent biological samples from two replicate experiments.…”
Section: Real-time Quantitative Rt-pcrmentioning
confidence: 99%
“…A microsomal protein fraction of G. intraradices was extracted as previously described (Benabdellah et al, 2009). Briefly, extraradical mycelium of G. intraradices was homogenized with a pestle and mortar in a cold homogenization buffer (1:2, w/v) consisting of 25 mM Tris-HCl pH 7.5, 250 mM sucrose, 2 mM EDTA pH 8, 1 mM PMSF and 10% PVPP (w/v).…”
Section: Isolation Of Microsomesmentioning
confidence: 99%
“…These proteins included Zn transporters, metallothioneins, heat shock protein (HSP) 90 and glutathione, which can be involved in the alleviation of ROS-induced damage (Hildebrandt et al, 2007). Finally, Benabdellah et al (2009) reported that GintGRX1, the first glomeromycotan dithiol glutaredoxin gene identified in an AM fungus, Rhizophagus irregularis (syn. Glomus intraradices), might play a role in protecting fungi against oxidative damage caused by trace elements.…”
Section: Introductionmentioning
confidence: 98%